Sildenafil alters biogenic amines and increases oxidative damage in brain regions of insulin-hypoglycemic rats - Guzmán David Calderón; Brizuela Norma Osnaya; Herrera Maribel Ortíz; Peraza Armando Valenzuela; Mejía Gerardo Barragán; Olguín Hugo Juárez; Jiménez Francisca Trujillo (Acta Pharmaceutica)
The aim of the present study was to determine the effect of sildenafil on dopamine, 5-hydroxyindol acetic acid (5-HIAA) and selected biomarkers of oxidative stress in the brain of hypoglycemic rats. The animals were treated intraperitoneally as follows: group 1 (control), saline solution; group 2, insulin (10 U per rat or 50 U kg−1); group 3, insulin + single dose of sildenafil (50 U kg−1 + 50 mg kg–1); group 4, insulin + three doses of sildenafil every 24 hours (50 U kg−1 + 50 mg kg−1). In groups 2, 3 and 4, insulin was administered every 24 hours for 10 days. Blood glucose was measured after the last treatment. On the last day of the treatment, the animals´ brains were extracted to measure the levels of oxidative stress markers [H2O2, Ca2+,Mg2+-ATPase, glutathione and lipid peroxidation (TBARS)], dopamine and 5-HIAA in the cortex, striatum and cerebellum/medulla oblongata by validated methods. The results suggest that administration of insulin in combination with sildenafil induces hypoglycemia and hypotension, enhances oxidative damage and provokes changes in the brain metabolism of biogenic amines. Administration of insulin and sildenafil promotes biometabolic responses in glucose control, namely, it induces hypoglycemia and hypotension. It also enhances oxidative damage and provokes changes in the brain metabolism of biogenic amines.